Anti-tumor Activity of Toll-Like Receptor 7 Agonists - Huju Chi; Chunman Li; Flora Sha Zhao; Li Zhang; Tzi Bun Ng; Guangyi Jin; Ou Sha (Frontiers Media S.A., 2017)
Toll-like receptors (TLRs) are a class of pattern recognition receptors that play a bridging role in innate immunity and adaptive immunity. The activated TLRs not only induce inflammatory responses, but also elicit the development of antigen specific immunity. TLR7, a member of TLR family, is an intracellular receptor expressed on the membrane of endosomes. TLR7 can be triggered not only by ssRNA during viral infections, but also by immune modifiers that share a similar structure to nucleosides. Its powerful immune stimulatory action can be potentially used in the anti-tumor therapy. This article reviewed the anti-tumor activity and mechanism of TLR7 agonists that are frequently applied in preclinical and clinical investigations, and mainly focused on small synthetic molecules, including imiquimod, resiquimod, gardiquimod, and 852A, etc.